2014
DOI: 10.1038/srep07037
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of grain boundaries and size effects in thermal conductivity of nanocrystalline materials

Abstract: A theoretical model for describing effective thermal conductivity (ETC) of nanocrystalline materials has been proposed, so that the ETC can be easily obtained from its grain size, single crystal thermal conductivity, single crystal phonon mean free path (PMFP), and the Kaptiza thermal resistance. In addition, the relative importance between grain boundaries (GBs) and size effects on the ETC of nanocrystalline diamond at 300 K has been studied. It has been demonstrated that with increasing grain size, both GBs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 37 publications
5
91
0
Order By: Relevance
“…It is well known that thermal conductivity of crystalline materials is lower than that of the corresponding single crystal materials, and it decreases as grain sizes decrease; different theoretical models have been proposed, and a critical review can be found in [38]. Anyway, it is commonly assumed that the correlation between incoming and outgoing phonons is completely destroyed by the scattering occurring at an interface [39] (e.g., a grain boundary).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that thermal conductivity of crystalline materials is lower than that of the corresponding single crystal materials, and it decreases as grain sizes decrease; different theoretical models have been proposed, and a critical review can be found in [38]. Anyway, it is commonly assumed that the correlation between incoming and outgoing phonons is completely destroyed by the scattering occurring at an interface [39] (e.g., a grain boundary).…”
Section: Resultsmentioning
confidence: 99%
“…There are many analytical models available in the literature that describe the effects of material geometry on κ, either in the presence of grain boundaries, 71,72,78,79 or pores. 75,76,80,81,82 These are based on simple geometrical considerations, and assume uniformity of the corresponding features, but in the case of non-uniformities, or in the presence of two or more types of nanosized features, their accuracy fades.…”
Section: Analytical Models -Extensions and Validationmentioning
confidence: 99%
“…This can enhance thermal transport in some devices based on nanostructures such as nano/microelectrical chips or improve efficiency of thermoelectric conversion. Besides some experimental attempts [21][22][23], theoretical modeling performs a significant role to predict the thermal conductivity of bulk silicon and also silicon nanostructures containing vacancies [24][25][26][27][28][29], impurities [30][31][32] and grain boundaries [33,34].…”
Section: Introductionmentioning
confidence: 99%